1991
DOI: 10.1115/1.2899614
|View full text |Cite
|
Sign up to set email alerts
|

Group Technology Production Methods in Manufacture

Abstract: Tolerance analysis and its impact on design, assembly, and manufacturing cost is the focus of Bjorke's book. It begins with a review of probability models applied to modeling tolerance chains, the main analysis tool. If you have had a course in probability and statistics, the concepts will probably be familiar to you, but if not this may be a difficult book to follow. Topics covered in early chapters are weighted heavily to linearizing and mathematically modeling simple chain links. Methods for determining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…In recent years, design of work around groups or teams, rather than at the level of the individual worker, has become more popular (Goodman et al 1987;Guzzo and Shea 1992;Hollenbeck et al 1995;Tannenbaum et al 1996). New manufacturing systems and advancements in understanding of team processes have encouraged the use of team approaches (Gallagher and Knight 1986;Majchrzak 1988).…”
Section: Team Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, design of work around groups or teams, rather than at the level of the individual worker, has become more popular (Goodman et al 1987;Guzzo and Shea 1992;Hollenbeck et al 1995;Tannenbaum et al 1996). New manufacturing systems and advancements in understanding of team processes have encouraged the use of team approaches (Gallagher and Knight 1986;Majchrzak 1988).…”
Section: Team Designmentioning
confidence: 99%
“…The number one obstacle to implementation was considered to be resistance to change (Hyer 1984). Guidelines for reducing resistance to change include the following (Gallagher and Knight 1986;Majchrzak 1988;Turnage 1990):…”
Section: Overcoming Resistance To Changementioning
confidence: 99%
“…CM provides the possibility of improving the quality of working life in two ways, by the use of job enrichment and by the creation of autonomous or self-managing groups [38]. Indian manufacturing sector is very vast and diversified and therefore the findings of any study, based on a small sample may not generalize any specific sector.…”
Section: Discussionmentioning
confidence: 96%
“…Although the minimum score is 3.27 (important to very important), GT is a technological improvement, and it is from this class of change that companies gain the largest manufacturing productivity increases. Manufacturing productivity has been found to be influenced by three major factors [38]: (i) 15% can be attributed to improvements in the quality of the work-force.…”
Section: Enablers Of Implementation Of Cms In Indian Industriesmentioning
confidence: 99%
“…It has been found that CMS can increase the productivity of manufacturing system by three major factors [2]:…”
Section: Introductionmentioning
confidence: 99%